Ler e escrever na Educação Infantil: análise de uma proposta curricular - Russo Marinho, Giulianny (2016)
This essay discusses the ways in which a primary school can organize its Language Practices Curriculum, working on reading and writing, without schooling and, at the same time, preserving the segment’s identity. Therefore, were analyzed a school’s curriculum, documents and annual; organization, as well as its teachers’ weekly planning. The analysis showd that it is possible to maintain a balance between knowledge and playing – a necessity inherent to this age group –due to theoretical and practical coherence, to established institutional conditions that favor reflection and to the formation of a crew, as well as a constant curricular development.